RELATIONSHIP BETWEEN DIGITAL GREEN ADVERTISING AND CORPORATE ENVIRONMENTAL RESPONSIBILITY PRACTICES IN THE NIGERIAN MANUFACTURING SECTOR (UNIZIK Journal of Marketing, 2025)
The study examined the relationship between digital green advertising and corporate environmental responsibility practices in the Nigerian Manufacturing Sector. Specifically, the study investigated the relationship between environmental claims and cooperate environmental responsibility practices in the Nigerian Manufacturing Sector. It also investigated the relationship between transparency and engagement and cooperate environmental responsibility practices in the Nigerian Manufacturing Sector. Two null hypotheses were tested at 0.05 level of significance. The correlational survey design was adopted for the study. A sample of 210 respondents were selected from 70 registered manufacturing firms using purposive sampling. Data were collected through a structured questionnaire and analysed using Pearson Product-Moment Correlation Coefficient. Findings revealed a significant positive relationship between environmental claims and corporate environmental responsibility practices, and also between transparency and engagement and corporate environmental responsibility practices. The study revealed that digital green advertising, when conducted with sincerity and accountability is positively related to corporate environmental responsibility practices among Nigerian manufacturing enterprises. Based on the findings, recommendations were made for manufacturing firms to strengthen the credibility of their green advertising strategies and adopt transparent stakeholder engagement as a core element of sustainability communication.
Keywords: Digital Green Advertising, Environmental Claims, Transparency and Engagement, Corporate Environmental Responsibility, Nigerian Manufacturing Sector